Efektifitas Layanan Bimbingan Kelompok untuk Mengurangi Perilaku Bullying bagi Siswa Kelas VIII.5 SMP N 1 Kec. Payakumbuh - Melandi Oktari; Syawaluddin Syawaluddin; Itrawati Itrawati (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
This research began with several students at SMPN 1 Kec. Payakumbuh in class VIII.5 who bullied his classmates. This bullying behavior is carried out individually and in groups, what is done is often calling friends by their parents' names, physically insulting friends and influencing other friends not to be friends with the victim, they even make the victim uncomfortable studying in class. Researchers try to implement group guidance services to reduce students' bullying behavior. This research aims to reduce student bullying behavior. The one group pre-test post-test pre-experiment method was used in this research. The research subjects were students in class VIII.5 who had bullying behavior obtained from the results of observations and interviews. The data analysis technique uses the Wilcoxon signed rank test. The instrument used is a measurement scale in the form of a questionnaire or questionnaire. The research results were seen from the implementation of the pre-test and post-test with a decrease in bullying behavior for each student. Wilcoxon signed rank test analysis shows that the value of 0.012 is lower than 0.05, so it can be concluded that there is a decrease in bullying behavior after being given group guidance treatment at SMPN 1 Kec. Payakumbuh.